Analisis Sentimen Keluhan Pelanggan ISP menggunakan Support Vector Machine (SVM) dan TF-IDF - Dini Fakta Sari; Deborah Kurniawati; Endang Wahyuningsih; Tediyan Rahmat Wibowo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the sentiment of customer complaints regarding Internet Service Provider (ISP) services in Indonesia, where the primary issues frequently reported include connection disruptions, slow internet speeds, weak signals, and unresponsive or uninformative complaint handling, as reflected in various consumer reports on social media. These issues contribute to customer dissatisfaction and necessitate data analysis solutions to deeply understand public opinions. Data was collected via API from a social media platform using keywords related to internet services, such as